2010
DOI: 10.1007/s12522-010-0047-4
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of possible criteria for elective single embryo transfer

Abstract: Purpose A major problem of assisted reproductive technology (ART) is multiple gestation, which impacts neonatal and perinatal medicine. The literature contains a number of reports that elective single embryo transfer (eSET) is effective for the control of multiple pregnancies; however, to date, uniform criteria have not been established. Methods Using logistic regression analysis based on the results of ART in our department from January 2005 to July 2006, our eSET criteria were established. We conducted a com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Forty-five studies [ 2 , 11 , 13 , 15 , 21 , 24 , 28 31 , 38 , 39 , 43 , 44 , 48 – 50 , 53 , 54 , 56 59 , 62 , 64 , 66 69 , 72 , 75 – 77 , 79 81 , 85 87 , 91 , 93 96 , 98 ] were pooled and found that the MPR was significantly lower in the SET group than in the DET group (0.05, 0.04–0.06, I 2 = 2%, P < 0.001) (Supplementary Fig. S2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Forty-five studies [ 2 , 11 , 13 , 15 , 21 , 24 , 28 31 , 38 , 39 , 43 , 44 , 48 – 50 , 53 , 54 , 56 59 , 62 , 64 , 66 69 , 72 , 75 – 77 , 79 81 , 85 87 , 91 , 93 96 , 98 ] were pooled and found that the MPR was significantly lower in the SET group than in the DET group (0.05, 0.04–0.06, I 2 = 2%, P < 0.001) (Supplementary Fig. S2 ).…”
Section: Resultsmentioning
confidence: 99%
“…S3 ). Forty-three studies [ 11 14 , 16 , 19 , 20 , 23 , 28 31 , 38 44 , 48 , 50 , 51 , 53 , 55 , 57 , 58 , 62 , 64 66 , 69 , 72 , 74 , 77 , 79 81 , 90 , 91 , 94 , 95 , 98 ] evaluated the miscarriage rates, and no significant difference was found between groups during the overall analysis (15.6% vs. 14.2%, 1.10, 0.95–1.27, I 2 = 30%, P = 0.211), neither in all the conducted subgroups (Supplementary Table S4 ). Seven studies [ 19 , 30 , 39 , 58 , 65 , 81 , 94 ] provided information on perinatal mortality, and no difference was observed (0.3% vs 0.7%, 0.71, 0.25–2.06, I 2 = 0%, P = 0.532).…”
Section: Resultsmentioning
confidence: 99%